2019
DOI: 10.1038/s41564-019-0626-z
|View full text |Cite
|
Sign up to set email alerts
|

Rapid MinION profiling of preterm microbiota and antimicrobial-resistant pathogens

Abstract: Accurate classification of a microbial mock community using MinION sequencing. We benchmarked MinION technology by profiling a bacterial mock community using R7.3 flow cells. Reads were analysed with NanoOK 18 and produced alignments to the 20 microbial reference sequences with 82-89% identity 19. Coverage ranged from almost 0 × (8 reads) of Actinomyces odontolyticus to 13 × (7,695 reads) of Streptococcus mutans, which is consistent with expected mock concentrations (Supplementary Table 1). Benchmarking to Ill… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
116
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(118 citation statements)
references
References 59 publications
2
116
0
Order By: Relevance
“…Norfolk and Norwich University Hospital), indicated a >50% reduction in NEC rates and late-onset sepsis when comparing 5year epochs before and after introducing probiotic supplementation, with no episodes of probiotic 'sepsis' indicated (P, 2019). Whilst the processes leading to life-threatening conditions including NEC in preterm infants are complex, overgrowth of potentially pathogenic bacteria is thought to be a key factor (Cassir et al, 2016;Leggett RM, 2019;Sim et al, 2015). We show that supplemented preterm infants have lower relative abundance of pathobionts including Klebsiella and Escherichia, which have previously been linked to NEC and late onset sepsis, and links to a recent study that performed MinION shotgun metagenomics and AMR profiling on samples from this cohort (Leggett RM, 2019).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Norfolk and Norwich University Hospital), indicated a >50% reduction in NEC rates and late-onset sepsis when comparing 5year epochs before and after introducing probiotic supplementation, with no episodes of probiotic 'sepsis' indicated (P, 2019). Whilst the processes leading to life-threatening conditions including NEC in preterm infants are complex, overgrowth of potentially pathogenic bacteria is thought to be a key factor (Cassir et al, 2016;Leggett RM, 2019;Sim et al, 2015). We show that supplemented preterm infants have lower relative abundance of pathobionts including Klebsiella and Escherichia, which have previously been linked to NEC and late onset sepsis, and links to a recent study that performed MinION shotgun metagenomics and AMR profiling on samples from this cohort (Leggett RM, 2019).…”
Section: Discussionsupporting
confidence: 67%
“…As Bif/Lacto infants were predominantly colonized by genus Bifidobacterium, this may have contributed to reduce the reservoir of potentially multidrug resistance pathogens (i.e. Staphylococcus, Escherichia, and Klebsiella), which were prevalent in Control infants, and which have previously been shown to harbour a large repertoire of AMR determinants (including in this cohort) (Leggett RM, 2019;Rowe et al, 2019).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Illumina) has been one of the main issues limiting the dissemination of this technology to broader fields. In microbial analysis however, several studies have revealed that the error rate has been somehow compensated by reads length, generating outputs comparable to Illumina 26,27,[45][46][47][48] , sharing more than 95% of total taxonomical abundance 49 . These studies support the robustness of the results achieved with this technology and together with the low initial cost and high portability of the device, suggests that it will be a preferred to other technologies for microbial studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite these advantages, when comparing to short reads sequencing such as Illumina, the error rate is higher 22 , problem that has been progressively mitigated with technological advances and better bioinformatic tools 24,25 . Regarding the study of microbiota, several studies have been dedicated to compare taxonomical analysis derived by this technology with Illumina sequencing, and have shown that error rate has been compensated with larger fragments, providing in some cases higher taxonomical resolution 26,27 . Although the error rate remains the main limitation to the expansion of this sequencing methodology, it has been successfully applied in several species and tissues, identifying the microbiota present in complex samples from terrestrial 28,29 and aquatic environment 23,30 .…”
mentioning
confidence: 99%